Interleukin-17: Potential Target for Chronic Wounds. (18th November 2019) - Hadian, Yasmin; Bagood, Michelle D.; Dahle, Sara E.; Sood, Apra; Isseroff, R. Rivkah
Abstract : Chronic wounds exhibit persistent inflammation with markedly delayed healing. The significant burden of chronic wounds, which are often resistant to standard therapy, prompts further research on novel therapies. Since the interleukin-17 family has been implicated as a group of proinflammatory cytokines in immune-mediated diseases in the gut and connective tissue, as well as inflammatory skin conditions, we consider here if it may contribute to the pathogenesis of chronic wounds. In this review, we discuss the interleukin-17 family's signaling pathways and role in tissue repair. A PubMed review of the English literature on interleukin-17, wound healing, chronic wounds, and inflammatory skin conditions was conducted. Interleukin-17 family signaling is reviewed in the context of tissue repair, and preclinical and clinical studies examining its role in the skin and other organ systems are critically reviewed. The published work supports a pathologic role for interleukin-17 family members in chronic wounds, though this needs to be more conclusively proven. Clinical studies using monoclonal interleukin-17 antibodies to improve healing of chronic skin wounds have not yet been performed, and only a few studies have examined interleukin-17 family expression in chronic skin wounds. Furthermore, different interleukin-17 family members could be playing selective roles in the repair process. These studies suggest a therapeutic role for targeting interleukin-17A to promote wound healing; therefore, interleukin-17A may be a target worthy of pursuing in the near future.